Investigating the human condition through the sculpted figure: exploring the artworks of Jane Alexander, Camille Claudel, Rook Floro, and William Kentridge - Holzer, Manuela (Stellenbosch : Stellenbosch University, 2016)
Thesis (MA)--Stellenbosch University, 2016.